Immune related adverse events and treatment discontinuation in patients older and younger than 75 years with advanced melanoma receiving nivolumab or pembrolizumab. Issue 2 (March 2022) - Ksienski, Doran; Truong, Pauline T.; Croteau, Nicole S.; Chan, Angela; Sonke, Eric; Patterson, Tiffany; Clarkson, Melissa; Hackett, Samuel; Lesperance, Mary
Abstract: Background: Programmed cell-death 1 antibodies (PD-1 Ab) improve overall survival (OS) for patients with advanced melanoma in trials; however, safety data in patients ≥75 years are lacking. The prognostic significance of and risk factors for PD-1 Ab discontinuation due immune related adverse events (irAE) are also uncertain. Methods: Patients with advanced melanoma receiving frontline PD-1 Ab at British Columbia Cancer outside of clinical trials between 10/2015–10/2019 were retrospectively analyzed. The incidence and subtypes of irAE were compared between age subgroups <75 and ≥ 75 years. Univariable logistic regression identified variables associated with treatment discontinuation within four months of PD-1 Ab initiation. Cox proportional hazard regression models were used to determine factors significantly associated with OS. Results: 302 patients were identified, of whom 126 (41.7%) were ≥ 75 years. During all follow-up, 15.9% of patients experienced irAE grade 3/4 and 27.2% of the cohort stopped PD-1 Ab due to immune toxicity. irAE incidence, hospitalization, and need for steroids by the four-month landmark were similar amongst age groups. Advanced age was not associated with risk of PD-1 Ab discontinuation from irAE on logistic regression. For the entire cohort, pre-treatment factors associated with shorter OS on multivariable analysis were ECOG performance status ≥1, M1d stage, lactate dehydrogenase >224, and neutrophil/ lymphocyte ratio ≥ 5. On four-month landmark multivariable analysis, treatment discontinuation due to irAE was significantly associated with worse OS. Conclusion: Patients aged ≥75 years experienced similar irAE rates and treatment discontinuation for immune toxicity compared to younger patients. As PD-1 Ab discontinuation due to irAE was associated with shorter OS, efforts to treat irAE early are warranted to potentially avoid therapy cessation.